Kesadaran Keamanan Informasi atas Phising, Smishing, dan Vishing pada Warga Kota Cimahi - ULFA LADAYYA; Deni Prayitno; Mamay Syani; Rizki Hikmawan; Nuur Wachid Abdulmajid (FKOM UNIKU, 2024)
Maintaining the confidentiality of information poses a significant challenge in today's technology-driven era. Information security is invaluable for individuals, businesses, governments, and global entities alike. It serves as a vital tool in preventing and identifying fraud within information-based systems. This knowledge is intended to educate people worldwide early on, helping them avoid falling victim to fraud. As technology advances for the greater good, it demands our vigilance against potential crimes like phishing, smishing, and vishing. The study utilized survey and literature review methods. Surveys were conducted using questionnaires at the Civil Registration Office of Cimahi City, targeting city residents. Survey findings indicated that many residents had experienced smishing incidents. Some respondents showed a commendable level of awareness regarding information security. Furthermore, the Dilandacita website aids respondents in handling population and civil registration matters efficiently.